Retail Concentration: The Shopping Streets - Passaro, Pierluigi; Salomone, Sergio; Petruzzellis, Luca (European Scientific Journal, ESJ, 2016)
Changes in consumer lifestyle strongly affect the retail demand, forcing the distribution system to reorganize and reposition its offer. Shopping proves to be a differentiating â€œactivityâ€, given that buying behavior is even more characterized by psychological and emotional factors, thus the purchased goods and the stores patronized become lifestyle symbols. However, a dualism between the retail dynamic needs and the existing spatial conditions exists. The former, especially in the case of fashion and shopping goods, requires a strategic position as close to customers as possible, namely huge spaces, attractive locations where the consumer need for experience and entertainment is met. The latter could be modified gradually and partially, determining a location hierarchy that results from wider changes in politics, economy and society. Consequently, all cities are experiencing a renewal process in their shopping â€œspacesâ€; retailers are competing for a front space on the streets in order to gain more visibility â€“ through huge and sparkling stores - and â€œlabelâ€ their products through values, symbols, and emotional/entertaining experience. This paper investigates the spatial/territorial dimension of consumption, analyzing the concentration phenomenon among shops from the same sector or complementary ones. By exploiting agglomeration economies shops can be positioned in the consumersâ€™ mind, firstly, with the streetâ€™s collective image and then with the shopâ€™s specific image. The purpose of this study is to determine the extent to which shopping streets (also referred to as the high street, downtown or city centre) provide retail concentration.